PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP PEROLEHAN SISA HASIL USAHA (SHU) PADA KSP KOPDIT GURU KELUBAGOLIT CABANG UTAMA ADONARA - Moi, Margareta Isabela; Thalib, Sabra B. Wahab; Ismail, Nuraini (Program Studi Akuntansi Universitas Flores, 2025)
This research aims to (1) determine the effect of own capital on the acquisition of remaining business result at the KSP Kopdit Guru Kelubagolit main branch of Adonara adan (2) determine the effect of loan capital on the acquisition of remaining business result at the KSP Kopdit Guru Kelubagolit main branch of Adonara. This Type of research is quantitative research. Data collection techniques use observation, interviews, documentation and literature study. Data analysis techniques are carried out using computer assistance, namely the SPSS Program. The results of the research show that (1) own capital partially influences the acquisition of remaining business result. This is proven by the t-count>t-table value (9,351<2,002) and the significance level isi 0,005<0,05, (2) borrowed capital is partial effect on the remaining business results. This is proven by the t-count>t-table (3,346<0,002) and the significance level is 0,023<0,05. Simultaneously, the variables of own capital and loan capital on the remaining business results are 64% while the remaining 36% is influenced by other factors outside the model.